STRATEGI PROMOSI MELALUI INSTAGRAM @evodis.aroma DALAM MENARIK MINAT BELI KONSUMEN - Fajar Muttaqin; Suparman; Amiruddin Saleh; Rici Tri Harpin Pranata; Nabhila Manisya; Khalila Zahra Maharani; Maharani Azzahra (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study aims to examine the promotional strategies implemented through social media content on Instagram @evodis.aroma to enhance consumer purchase interest. Beyond this, the research seeks to identify the range and diversity of content types used by the @evodis.aroma Instagram account to attract its audience and drive engagement. By employing a descriptive qualitative research method, utilizing in-depth interviews as a primary data collection technique, this study offers a comprehensive and nuanced understanding of the promotional tactics and content strategies deployed. The findings of this research reveal that Instagram @evodis.aroma utilizes a targeted promotional approach, strategically crafted to boost consumer interest and purchasing intent. This strategy is manifested through a variety of key elements and structured phases in the account’s content management, such as visually appealing posts, interactive stories, and informative product highlights. The analysis process of the strategy used by Instagram @evodis.aroma is conducted using the AIDA model (Awareness, Interest, Desire, and Action) as the main guideline.